Disputas pelos sentidos do estupro no controle da publicidade brasileira: o comercial "invisível" da nova schin sob perspectivas feministas e da análise crítica do discurso - Fernandes, Leonísia Moura (2018)
In recent years, the discussion about the high rates of sexual violence against women has gained visibility in Brazil, generating diverse interpretations, many of which blame the victims, including cases of incitement to violence and its consequent naturalization. Feminists and women's movements use the term "rape culture" to name this phenomenon and call attention to the fact that it is present in all sorts of fields and social institutions, including commercial advertising, which exercises a central role in the current phase of monopoly capitalism. From feminist perspectives and cultural studies, this paper aims to understand how sexual violence against women can integrate a culture of a society, taking into account the power structures that organize it. To do so, the methodological approach proposed by the Critical Discourse Analysis (ACD) is used to interpret the dispute of meanings of sexual violence mobilized by a commercial of the Nova Schin beer brand, that, in 2012, triggered hundreds of denunciations to the Conselho Nacional de Autorregulamentação Publicitária (CONAR), in addition to street demonstrations in Brazil. The corpus of analysis corresponds, therefore, to the commercial and the two representations that were processed in the CONAR from the denunciations. It discusses which ideologies the different discourses on sexual violence against women are linked to and how they relate to their confrontation and to the struggle for gender equality.